Bacteriostatic aluminum-based lithium adsorbent and preparation method thereof

By preparing antibacterial aluminum-based lithium adsorbents during lithium extraction in the salt lake, using guanidine polymer PEIGH grafting technology, the problems of reduced adsorbent efficiency and high cost caused by microbial contamination are solved, and efficient microbial inhibition and adsorption are achieved Lithium extraction effect.

CN119186483APending Publication Date: 2024-12-27QINGHAI TAIFENG XIANXING LITHIUM ENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411507236.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Microbial pollution during lithium extraction in the salt lake leads to bioenrichment of adsorbent interfaces, reducing mass transfer efficiency and increasing operating costs. The existing solutions are expensive to invest and maintain, and it is difficult to effectively control microbial growth.

Method used

A method for preparing antibacterial aluminum-based lithium adsorbent is adopted. By mixing the lithium source and the aluminum source solution, the pH is adjusted, and a constant temperature water bath reaction is carried out. Then, the DA-Tris mixed aqueous solution is prepared using dopamine hydrochloride and tris(hydroxymethyl)aminomethane. The granulated adsorbent is modified, and the guanidine polymer PEIGH is prepared by reaction of polyethyleneimine and guanidine hydrochloride, and grafted to the surface of aluminum-based lithium adsorbent to impart antibacterial properties.

Benefits of technology

The antibacterial rate has been significantly improved to 99.5%, significantly improved the antimicrobial pollution ability, extended the service life of adsorbents, reduced the cost of lithium extraction projects, and improved the efficiency of adsorption and lithium extraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186483A_ABST
    Figure CN119186483A_ABST
Patent Text Reader

Abstract

The invention discloses a bacteriostatic aluminum-based lithium adsorbent and a preparation method thereof, and belongs to the technical field of lithium extraction and adsorption of salt lakes. In order to solve the problem of pollution caused by microorganism growth in an adsorption lithium extraction project, aluminum-based adsorbent powder is prepared on the basis of a lithium source and an aluminum source, and a granulation adsorbent is obtained through granulation; preparing a DA-Tris mixed aqueous solution based on dopamine hydrochloride and tris (hydroxymethyl) aminomethane; the preparation method comprises the following steps: infiltrating a granulation adsorbent in a DA-Tris mixed aqueous solution for reaction to obtain a preliminarily modified aluminum-based lithium adsorbent; the preparation method comprises the following steps: reacting polyethyleneimine with guanidine hydrochloride to prepare a guanidyl polymer PEIGH; the primarily modified aluminum-based lithium adsorbent is soaked in a PEIGH aqueous solution for reaction, and the bacteriostatic aluminum-based lithium adsorbent is obtained. The prepared aluminum-based lithium adsorbent has good antibacterial and anti-pollution performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium extraction and adsorption in salt lakes, and specifically relates to an antibacterial aluminum-based lithium adsorbent and a preparation method thereof. Background Art

[0002] Aluminum-based lithium adsorbents are widely used in the extraction of lithium from salt lake brine in Qinghai due to their simple preparation, fast adsorption speed, high selectivity, good recyclability and low dissolution loss. However, due to the natural presence of a certain amount of microorganisms in salt lake brine, these microorganisms are easy to multiply in large quantities at suitable pH and temperature, resulting in serious microbial contamination during the adsorption and lithium extraction process, causing microbial bioaccumulation at the adsorbent interface, resulting in reduced mass transfer efficiency for adsorption and lithium extraction, increased operating costs, and shortened service life of lithium adsorbents and subsequent materials in the process. At present, the common engineering solution for microbial contamination control in salt lake lithium extraction projects is to add an ultrafiltration process to the front end of the adsorption process. Although it can improve the efficiency of adsorption and lithium extraction to a certain extent, the investment and operation and maintenance costs of ultrafiltration projects are high; in addition, adding sodium hypochlorite bactericidal agents to the inlet brine can also limit the growth of microorganisms, but this solution often requires the addition of reducing agents or activated carbon processes to remove excess residual chlorine, otherwise it will lead to serious desalination rate decline in the subsequent nanofiltration process. In summary, improving the anti-microbial fouling ability of aluminum-based lithium adsorbents is the most cost-effective microbial control engineering solution. The development of antibacterial lithium adsorbents has important strategic value and economic significance in salt lake adsorption and lithium extraction projects. Summary of the invention

[0003] In order to solve the pollution problem caused by the growth of microorganisms in the adsorption and lithium extraction project, the present invention provides an antibacterial aluminum-based lithium adsorbent and a preparation method thereof.

[0004] The technical solution adopted by the present invention to solve its technical problem is:

[0005] A method for preparing an antibacterial aluminum-based lithium adsorbent comprises the following steps:

[0006] 1) mixing a lithium source solution and an aluminum source solution, adding hydrochloric acid to adjust the pH to weak acidity after stabilization, and then reacting in a constant temperature water bath, aging after the reaction is complete, filtering and drying the obtained powder to obtain an aluminum-based adsorbent powder;

[0007] 2) granulating the aluminum-based adsorbent powder to obtain a granulated adsorbent;

[0008] 3) preparing a DA-Tris mixed aqueous solution from dopamine hydrochloride (DA) and tris(hydroxymethyl)aminomethane (Tris);

[0009] 4) soaking the granulated adsorbent in a DA-Tris mixed aqueous solution for reaction, and washing with deionized water after the reaction is completed to obtain a preliminary modified aluminum-based lithium adsorbent;

[0010] 5) preparing a guanidine-based polymer PEIGH (polyethyleneimine guanidine hydrochloride) by reacting polyethyleneimine (PEI) and guanidine hydrochloride (GH);

[0011] 6) The preliminary modified aluminum-based lithium adsorbent is immersed in a PEIGH aqueous solution for reaction, and after the reaction is completed, it is rinsed with deionized water to obtain the final antibacterial aluminum-based lithium adsorbent.

[0012] Furthermore, in step 1), the lithium source is one or more of lithium chloride, lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, and lithium sulfate, and the total lithium concentration of the lithium source solution is 1 to 2 mol / L.

[0013] Furthermore, in step 1), the aluminum source is one or more of aluminum chloride, sodium aluminate, aluminum nitrate, PAC, and aluminum sulfate, and the concentration of the aluminum source solution is 1 to 3 mol / L.

[0014] Furthermore, in step 1), the lithium source solution and the aluminum source solution are mixed in a mass ratio of the lithium source to the aluminum source of 1:1 to 1:1.2.

[0015] Furthermore, in step 1), the pH is adjusted to 5.0-7.0, and the reaction is carried out in a constant temperature water bath at 50-80° C. for 4-12 hours.

[0016] Furthermore, the aging in step 1) is performed for 12 to 24 hours.

[0017] Furthermore, in step 2), the adsorbent powder is granulated by the NIPS method, and the base material used for granulation is one or more of PVC, PVDF, PSF, PTFE, PAN, and PMMA.

[0018] Furthermore, the method for preparing the DA-Tris mixed aqueous solution in step 3) is: mixing dopamine hydrochloride with a concentration of 0.5-1.2 g / L and tris(hydroxymethyl)aminomethane with a concentration of 1-1.5 g / L, and then controlling the pH to 8-9 and the solid-liquid ratio to 1:20-1:50.

[0019] Furthermore, the reaction time in step 4) is 1 to 2 hours.

[0020] Furthermore, the method for preparing polyethyleneimineguanidine hydrochloride in step 5) is: polyethyleneimine and guanidine hydrochloride are added into a three-necked flask in a mass ratio of 1 to 2:1, heated to 70 to 90°C for reaction for 1 to 3 hours under mechanical stirring, and then continued to heat to 100 to 180°C for reaction for 2 to 4 hours; the reaction process is carried out under nitrogen protection, and the ammonia generated during the reaction is absorbed by dilute hydrochloric acid.

[0021] Furthermore, in step 6), the mass fraction of the PEIGH aqueous solution is 3% to 4%, and the reaction is carried out at room temperature for 1 to 2 hours.

[0022] An antibacterial aluminum-based lithium adsorbent is prepared by the above preparation method.

[0023] Beneficial effects achieved by the present invention:

[0024] Guanidine polymer PEIGH is a cationic bactericide that can ionize to form positively charged groups under physiological conditions. The outer layer of bacterial and fungal cell membranes is electronegative, and the guanidine group interacts with bacterial cells through electrostatic attraction, eventually causing the cell membrane to rupture and kill the bacteria. The present invention first prepares a preliminary modified aluminum-based lithium adsorbent, and then prepares a light yellow viscous solid guanidine polymer PEIGH. Innovatively, the two react, and then dopamine hydrochloride is used as an intermediate layer to successfully graft the guanidine polymer PEIGH to the surface of the aluminum-based lithium adsorbent, giving the aluminum-based lithium adsorbent good antibacterial and anti-pollution properties. Compared with traditional commercial aluminum-based lithium adsorbents, the antibacterial aluminum-based lithium adsorbent prepared by the present invention has an antibacterial rate of up to 99.5%, and its ability to resist microbial contamination is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The material flow chart of the present invention for preparing the antibacterial aluminum-based lithium adsorbent.

[0026] Figure 2 This is the NMR graph of PEIGH and its precursor PEI in the antibacterial aluminum-based lithium adsorbent prepared in Example 1.

[0027] Figure 3 This is a comparison chart of the changes in long-term lithium adsorption capacity of two aluminum-based lithium adsorbents.

[0028] Figure 4 This is a control experiment chart for inhibiting microorganisms in water. DETAILED DESCRIPTION

[0029] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.

[0030] Embodiment 1:

[0031] 1) The lithium source solution is a mixed solution of lithium chloride and lithium hydroxide, and the total lithium concentration is 1.5 mol / L. The aluminum source solution is an aluminum chloride solution with a concentration of 2 mol / L. After the two solutions are slowly mixed and stabilized, hydrochloric acid is added to adjust the pH to 6.0, and then reacted in a constant temperature water bath at 60°C for 8 hours, aged for 18 hours after the reaction, filtered and dried to obtain an aluminum-based adsorbent powder.

[0032] 2) The aluminum-based adsorbent powder is granulated by the NIPS method, and PVC is selected as the granulation substrate to obtain the granulated adsorbent.

[0033] 3) Weigh 0.8 g / L DA and 1.2 g / L Tris, mix them, control the solid-liquid ratio at 1:30, and control the pH at 8 to prepare a DA-Tris mixed aqueous solution.

[0034] 4) The granulated adsorbent was immersed in a DA-Tris mixed aqueous solution for reaction for 1 hour. After the reaction was completed, it was rinsed with deionized water for 3 times to obtain a preliminary modified aluminum-based lithium adsorbent.

[0035] 5) PEI and GH were added to a three-necked flask in a mass ratio of 1:1, heated to 90°C for 2 hours under mechanical stirring, and then continued to heat to 160°C for 4 hours. The reaction process was carried out under nitrogen protection, and the ammonia generated during the reaction was absorbed by dilute hydrochloric acid. After the reaction, a light yellow viscous solid PEIGH was obtained. The synthesis route is as follows:

[0036]

[0037] 6) The preliminary modified aluminum-based lithium adsorbent was immersed in a 3% by mass PEIGH aqueous solution for reaction for 2 hours. After the reaction was completed, it was rinsed with deionized water for 3 times to obtain the final antibacterial aluminum-based lithium adsorbent.

[0038] Embodiment 2:

[0039] 1) The lithium source solution is a mixed solution of lithium chloride and lithium hydroxide, and the total lithium concentration is 2 mol / L. The aluminum source solution is an aluminum chloride solution with a concentration of 3 mol / L. After the two solutions are slowly mixed and stabilized, hydrochloric acid is added to adjust the pH to 5.0, and then reacted at a constant temperature water bath at 50°C for 12 hours, aged for 12 hours after the reaction, filtered and dried to obtain an aluminum-based adsorbent powder.

[0040] 2) The aluminum-based adsorbent powder is granulated by the NIPS method, and PVC is selected as the granulation substrate to obtain the granulated adsorbent.

[0041] 3) Weigh 1.2 g / L DA and 1.5 g / L Tris, mix them, control the solid-liquid ratio at 1:20, and control the pH at 8 to prepare a DA-Tris mixed aqueous solution.

[0042] 4) The granulated adsorbent was immersed in a DA-Tris mixed aqueous solution for reaction for 2 hours. After the reaction was completed, it was rinsed with deionized water for 3 times to obtain a preliminary modified aluminum-based lithium adsorbent.

[0043] 5) PEI and GH were added into a three-necked flask in a mass ratio of 1:1, heated to 80°C for reaction for 1 h under mechanical stirring, and then continued to heat to 180°C for reaction for 2 h. The reaction process was carried out under nitrogen protection, and the ammonia generated during the reaction was absorbed by dilute hydrochloric acid. After the reaction, a light yellow viscous solid PEIGH was obtained.

[0044] 6) The preliminary modified aluminum-based lithium adsorbent was immersed in a 4% by mass PEIGH aqueous solution for reaction for 2 hours. After the reaction was completed, it was rinsed with deionized water for 3 times to obtain the final antibacterial aluminum-based lithium adsorbent.

[0045] Embodiment 3:

[0046] 1) The lithium source solution is a mixed solution of lithium chloride and lithium hydroxide, and the total lithium concentration is 1 mol / L. The aluminum source solution is an aluminum chloride solution with a concentration of 1 mol / L. After the two solutions are slowly mixed and stabilized, hydrochloric acid is added to adjust the pH to 7.0, and then reacted at 80°C in a constant temperature water bath for 4 hours, aged for 24 hours after the reaction, filtered and dried to obtain an aluminum-based adsorbent powder.

[0047] 2) The aluminum-based adsorbent powder is granulated by the NIPS method, and PVC is selected as the granulation substrate to obtain the granulated adsorbent.

[0048] 3) Weigh 0.5 g / L DA and 1 g / L Tris, mix them, control the solid-liquid ratio at 1:50, and control the pH at 9 to prepare a DA-Tris mixed aqueous solution.

[0049] 4) The granulated adsorbent was immersed in a DA-Tris mixed aqueous solution for reaction for 1 hour. After the reaction was completed, it was rinsed with deionized water for 3 times to obtain a preliminary modified aluminum-based lithium adsorbent.

[0050] 5) PEI and GH were added into a three-necked flask in a mass ratio of 2:1, heated to 70°C for 3 h under mechanical stirring, and then continued to heat to 100°C for 3 h. The reaction process was carried out under nitrogen protection, and the ammonia generated during the reaction was absorbed by dilute hydrochloric acid. After the reaction, a light yellow viscous solid PEIGH was obtained.

[0051] 6) The preliminary modified aluminum-based lithium adsorbent was immersed in a 4% by mass PEIGH aqueous solution for reaction for 1 hour. After the reaction was completed, it was rinsed with deionized water for 3 times to obtain the final antibacterial aluminum-based lithium adsorbent.

[0052] The performance of the antibacterial aluminum-based lithium adsorbent prepared in Example 1 was tested as follows:

[0053] 1. NMR characterization:

[0054] The experiment used heavy water as solvent and further tested the NMR spectra of PEI and PEIGH, such as Figure 2 As shown. Figure 2 As shown in Figure (a), the -CH2- in the PEI chain segment is affected by the surrounding primary or secondary amine groups, and the chemical shift varies between 2.56 and 2.64. Figure 2 As shown in Figure (b), the chemical shift of -CH2- in the PEIGH segment increased to 3.24-3.89, which was due to the influence of the electron-withdrawing effect of the guanidine group, and the chemical shift further increased. This characterization strongly confirmed that the PEI and GH on the interface of the antibacterial aluminum-based lithium adsorbent underwent a polymerization reaction to generate the PEIGH active component.

[0055] 2. Verification of lithium extraction efficiency by adsorption:

[0056] Taking the brine of Jinaier Salt Lake in Dongtai, Qinghai as an example, the conventional unmodified aluminum-based lithium adsorbent and the antibacterial aluminum-based lithium adsorbent of the present invention were subjected to 100 cycles of lithium adsorption-analysis cycle test, and the change of lithium adsorption capacity and the microbial detection of the qualified solution were monitored at the same time. Figure 3 As shown. The results show that within 100 cycles of the test, the lithium adsorption capacity of the antibacterial aluminum-based lithium adsorbent was always maintained between 2.0 and 2.2 g / L, while the capacity of the traditional unmodified aluminum-based lithium adsorbent was significantly reduced from the initial 2.2 g / L to less than 1.3 g / L due to the growth of microorganisms, which resulted in the inability of brine to fully contact the adsorbent interface. This experiment strongly confirmed that the antibacterial aluminum-based lithium adsorbent of the present invention can significantly improve the efficiency of lithium adsorption engineering.

[0057] 3. Verification of microbial changes in brine:

[0058] The original halogen, the conventional unmodified aluminum-based lithium adsorbent and the antibacterial aluminum-based lithium adsorbent of the present invention were subjected to 100 cycles and the qualified liquid microorganisms were analyzed for detection. The microbial content is as follows Figure 4 As shown, Figure a shows the microbial content in the raw water, Figure b shows the microbial content in the water produced by the traditional unmodified aluminum-based lithium adsorbent, and Figure c shows the microbial content in the water produced by the antibacterial aluminum-based lithium adsorbent of the present invention. It can be seen from the test that compared with the microbial content in the raw water, the microbial content in the water produced by the traditional unmodified aluminum-based lithium adsorbent is significantly improved, while the microbial content in the water produced by the antibacterial aluminum-based lithium adsorbent of the present invention is almost zero, and the antibacterial rate is as high as 99.5%. This experiment directly confirms that the antibacterial aluminum-based lithium adsorbent of the present invention has a strong bactericidal and antibacterial effect, and can significantly inhibit the growth of microorganisms in brine, thereby streamlining the antibacterial process before and after adsorption and lithium extraction, greatly reducing the cost of lithium extraction engineering, and improving the engineering efficiency of raw brine adsorption and lithium extraction.

[0059] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing an antibacterial aluminum-based lithium adsorbent, characterized in that: The following steps are involved: 1) mixing a lithium source solution and an aluminum source solution, adding hydrochloric acid to adjust the pH to weak acidity after stabilization, and then reacting in a constant temperature water bath, aging after the reaction is complete, filtering and drying the obtained powder to obtain an aluminum-based adsorbent powder; 2) granulating the aluminum-based adsorbent powder to obtain a granulated adsorbent; 3) preparing a DA-Tris mixed aqueous solution from dopamine hydrochloride and tris(hydroxymethyl)aminomethane; 4) soaking the granulated adsorbent in a DA-Tris mixed aqueous solution for reaction, and washing with deionized water after the reaction is completed to obtain a preliminary modified aluminum-based lithium adsorbent; 5) preparing a guanidine-based polymer PEIGH by reacting polyethyleneimine and guanidine hydrochloride; 6) The preliminary modified aluminum-based lithium adsorbent is immersed in a PEIGH aqueous solution for reaction, and after the reaction is completed, it is rinsed with deionized water to obtain the final antibacterial aluminum-based lithium adsorbent.

2. The preparation method according to claim 1, characterized in that In step 1), the lithium source is one or more of lithium chloride, lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, and lithium sulfate, and the total lithium concentration of the lithium source solution is 1 to 2 mol / L; the aluminum source is one or more of aluminum chloride, sodium aluminate, aluminum nitrate, PAC, and aluminum sulfate, and the concentration of the aluminum source solution is 1 to 3 mol / L.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the lithium source solution and the aluminum source solution are mixed according to a mass ratio of the lithium source to the aluminum source of 1:1 to 1:1.

2.

4. The preparation method according to claim 1, characterized in that: In step 1), the pH is adjusted to 5.0-7.0, and the reaction conditions in a constant temperature water bath are 50-80° C. for 4-12 hours; and aging is performed for 12-24 hours.

5. The preparation method according to claim 1, characterized in that: In step 2), the adsorbent powder is granulated by the NIPS method, and the base material used for granulation is one or more of PVC, PVDF, PSF, PTFE, PAN, and PMMA.

6. The preparation method according to claim 1, characterized in that: The method for preparing the DA-Tris mixed aqueous solution in step 3) is: mixing dopamine hydrochloride with a concentration of 0.5-1.2 g / L and tris(hydroxymethyl)aminomethane with a concentration of 1-1.5 g / L, and then controlling the pH to 8-9 and the solid-liquid ratio to 1:20-1:

50.

7. The preparation method according to claim 1, characterized in that: The reaction time in step 4) is 1 to 2 hours.

8. The preparation method according to claim 1, characterized in that: The method for preparing polyethyleneimine guanidine hydrochloride in step 5) is: polyethyleneimine and guanidine hydrochloride are added into a three-necked flask in a mass ratio of 1 to 2:1, heated to 70 to 90°C for reaction for 1 to 3 hours under mechanical stirring, and then continued to heat to 100 to 180°C for reaction for 2 to 4 hours; the reaction process is carried out under nitrogen protection, and ammonia generated during the reaction is absorbed by dilute hydrochloric acid.

9. The preparation method according to claim 1, characterized in that: In step 6), the mass fraction of the PEIGH aqueous solution is 3% to 4%, and the reaction is carried out at room temperature for 1 to 2 hours.

10. An antibacterial aluminum-based lithium adsorbent, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.